Pengembangan Sistem Pembuangan Air Otomatis Perahu berbasis Tenaga Surya pada Kelompok Nelayan Kecamatan Johan Pahlawan Kabupaten Aceh Barat - Haimi Ardiansyah; Herdian Saputra; Fitrayansyah Fitrayansyah; Riza Hasan; Heri Wiharja.MS; Roni Agusmaniza; Abdiel Khaleil Akmal; Suja Ardiansyah; Yoel Cristian Simamora (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2026)
Rumoh Nelayan Aceh is a fishermen's association based in Johan Pahlawan sub-district, West Aceh Regency. Obstacles often faced by partners include the use of conventional boats with manual exhaust systems using diesel fuel pumps and some others still using hand pumps. The use of technology that is still minimal makes fishermen have to pay special attention to the disposal of water that enters the boat, this situation takes up the fisherman's time with a divided focus. The use of components that are not environmentally friendly Some fishing boats already use a diesel-powered boat water exhaust system. The use of fuel oil is not good from an economic point of view and results in emissions that have a negative impact on the environment. Lack of knowledge about the use of cutting-edge technology. With these conditions, this program aims to improve the efficiency of the fishing process, the use of automation technology, the use of environmentally friendly energy, reduce production costs, and encourage fishermen's independence in facing the challenges of the modern fishing world.